Role of Platelet Indices as a Potential Marker for Malaria Severity - Biruk Bayleyegn; Fikir Asrie; Aregawi Yalew; Berhanu Woldu (Journal of Parasitology Research)
Purpose. Platelet parameter alteration such as platelet count and platelet indices are more common than in other blood cell lines due to diverse causative pathophysiological mechanisms in severe malaria infection. In malaria patients, no more studies evaluated platelet indices in relation to disease severity and prognosis. Therefore, this review assessed the current scientific knowledge on the potential role of platelet indices for the diagnostic marker of severe malaria infection. Results. Hence, after reviewing recent literatures, elevation of mean platelet volume and platelet distribution width in addition to decreased plateletcrit and platelet counts is the known potential risk factor associated with warning signs of severe malaria. Thus, thrombocytopenia<150×109/L, MPV≥9.05 fL, and PDW≥14.550% as well as significantly higher P-LCR and decrease in PCT are shown significant sensitivity and specificity as they are used as diagnostic and prognostic values in severe malaria infection. Conclusion. Platelet indices are useful predictors of malaria severity. Immature platelet fraction (IPF%) is raised in the case of severe malaria, and it was significantly more useful than MPV. Advanced research will further investigate the platelet index abnormality associated with specific age and gender among specific malaria species.